2022
DOI: 10.3390/s22155628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Foot Center of Pressure Estimation from Pressure Insoles during Sidestep Cuts, Runs and Walks

Abstract: Estimating the foot center of pressure (CoP) position by pressure insoles appears to be an interesting technical solution to perform motion analysis beyond the force platforms surface area. The aim of this study was to estimate the CoP position from Moticon® pressure insoles during sidestep cuts, runs and walks. The CoP positions assessed from force platform data and from pressure insole data were compared. One calibration trial performed on the force platforms was used to localize the insoles in the reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The results of our study showed higher accuracy with lower error values in COPx (1.29 ± 0.47 mm in slower gait, 1.34 ± 0.47 mm in faster gait) compared to COPy (12.55 ± 5.08 mm in slower gait, 11.26 ± 3.89 mm in faster gait). Similar findings were reported in the studies by Zhang et al [ 22 ] and Morin et al [ 29 ]. According to their study results, locating the sensors at the top and bottom edges of the insole may be a method to minimize the error rate in COPy.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study showed higher accuracy with lower error values in COPx (1.29 ± 0.47 mm in slower gait, 1.34 ± 0.47 mm in faster gait) compared to COPy (12.55 ± 5.08 mm in slower gait, 11.26 ± 3.89 mm in faster gait). Similar findings were reported in the studies by Zhang et al [ 22 ] and Morin et al [ 29 ]. According to their study results, locating the sensors at the top and bottom edges of the insole may be a method to minimize the error rate in COPy.…”
Section: Discussionsupporting
confidence: 92%
“…This paper presented a novel Bi-LSTM structure that learns bidirectional temporal dependencies in sequential data (namely, the signals acquired from heterogeneous insole-embedded sensors) to accurately estimate underfoot COP trajectories. The proposed method can achieve comparable accuracy as research-grade commercial insole systems that rely on expensive, high-density pressure-sensitive arrays [11], [59], [60]. Furthermore, compared to physics-informed approaches such as [26], the proposed method does not require timeconsuming equilibration procedures (which must be with specialized equipment) improves the and applicability of the technology, while retaining interpretability.…”
Section: Discussionmentioning
confidence: 97%
“…The pressure sensors can be used to track foot pressure changes over a period, and this will help in evaluating the progress achieved. The information can be used to make changes to the resistance training program so that there can be better performance in the long term [ 66 ].…”
Section: Wearable Devices For Measuring Biomechanical Parameters Duri...mentioning
confidence: 99%